Careers in Chemistry exhibition display - Hercules Incorporated (1950)
General view of several unidentified individuals examining a "Careers in Chemistry" exhibition display highlighting the products and activities of the Hercules Powder Company. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Advertising; Advertising, Industrial; Corporations; Chemical industry; Hercules Incorporated; Vocational guidance